The Influence of Service Quality on Patient Satisfaction at Community Health Centers Salomekko, Bone Regency - Milanda Hafid; Moh. Haris Pasigai; Zalkha Soraya (Income Journal Of Economics Development, 2024)
This study aims to determine the effect of service quality on patient satisfaction at the Salomekko Health Center, Bone Regency. This study uses a quantitative approach. The subjects of this study were patients who came for treatment at the Salomekko Health Center, Bone Regency, and a sample of 50 people was taken. The data collection method used a questionnaire. The data analysis technique used is Simple Linear Regression Analysis using statistical calculations through the Statistical Package for the Social Science (SPSS) application. The results showed that Service Quality (X) had a positive and significant effect on Patient Satisfaction (Y), as seen from the results of t count> t table ((2.332.>1.676) and a significant value = 0.24 <0.05. This finding indicates that improving service quality at Salomekko Health Center is directly correlated with increasing patient satisfaction. The implications of this study emphasize the importance of continuous efforts in improving service quality in primary health facilities such as puskesmas. Improvements in aspects such as reliability, responsiveness, assurance, empathy, and physical evidence of service can significantly contribute to increased patient satisfaction. In addition, the results of this study can serve as a reference for the management of Puskesmas Salomekko and other health agencies in designing strategies to improve service quality that are more effective and oriented to patient needs.